Development of Various Photovoltaic‐Driven Water Electrolysis Technologies for Green Solar Hydrogen Generation. Issue 5 (22nd September 2021) - Calnan, Sonya; Bagacki, Rory; Bao, Fuxi; Dorbandt, Iris; Kemppainen, Erno; Schary, Christian; Schlatmann, Rutger; Leonardi, Marco; Lombardo, Salvatore A.; Milazzo, R. Gabriella; Privitera, Stefania M. S.; Bizzarri, Fabrizio; et al.
Abstract : Direct solar hydrogen generation via a combination of photovoltaics (PV) and water electrolysis can potentially ensure a sustainable energy supply while minimizing greenhouse emissions. The PECSYS project aims at demonstrating a solar‐driven electrochemical hydrogen generation system with an area >10 m 2 with high efficiency and at reasonable cost. Thermally integrated PV electrolyzers (ECs) using thin‐film silicon, undoped, and silver‐doped Cu(In, Ga)Se2 and silicon heterojunction PV combined with alkaline electrolysis to form one unit are developed on a prototype level with solar collection areas in the range from 64 to 2600 cm 2 with the solar‐to‐hydrogen (StH) efficiency ranging from ≈4 to 13%. Electrical direct coupling of PV modules to a proton exchange membrane EC to test the effects of bifaciality (730 cm 2 solar collection area) and to study the long‐term operation under outdoor conditions (10 m 2 collection area) is also investigated. In both cases, StH efficiencies exceeding 10% can be maintained over the test periods used. All the StH efficiencies reported are based on measured gas outflow using mass flow meters. Abstract : Directly coupled photovoltaic electrolyzers with different degrees of integration are presented. Thermally integrated prototypes using earth‐abundant materials achieve comparable or higher solar‐to‐hydrogen (StH) conversion efficiency, determined from product gas collection, than previously reported similarly sized devices. The highest average StH efficiency reported, to date, for solar collection areas above 1 m 2 without thermal integration is also demonstrated.